L’Italie de Dominique Fernandez : Voyage au bout de l’être - Maroua Derouiche (Carnets)
For Dominique Fernandez, the trip to Italy is thought out in connection with his quest for identity. Not only does it constitute a reconquest of the world, the Italian journey is also a regaining of the writer's self and an elucidation of his own mystery. In this context, the first trip to Pisa was a love at first sight. From then on, the artist would no longer hesitate to integrate his own myth into an emerging Italian topic. Southern Italy is presented as the most suitable place to reveal a sexual identity, repressed for a long time and to advocate the return to a utopian state of primitive androgyny.